Genetic control of seed shattering during African rice domestication - Lv, S.; Wu, W.; Wang, M.; Meyer, R.S.; Ndjiondjop, M.N.; Tan, L.; Zhou, H.; Zhang, J.; Fu, Y.; Cai, H.; Sun, C.; Wing, Rod A.; et al. (Springer, 2018)
Domestication represents a unique opportunity to study the evolutionary process. The elimination of seed dispersal traits was a key step in the evolution of cereal crops under domestication. Here, we show that ObSH3, a YABBY transcription factor, is required for the development of the seed abscission layer. Moreover, selecting a genomic segment deletion containing SH3 resulted in the loss of seed dispersal in populations of African cultivated rice (Oryza glaberrima Steud.). Functional characterization of SH3 and SH4 (another gene controlling seed shattering on chromosome 4) revealed that multiple genes can lead to a spectrum of non-shattering phenotypes, affecting other traits such as ease of threshing that may be important to tune across different agroecologies and postharvest practices. The molecular evolution analyses of SH3 and SH4 in a panel of 93 landraces provided unprecedented geographical detail of the domestication history of African rice, tracing multiple dispersals from a core heartland and introgression from local wild rice. The cloning of ObSH3 not only provides new insights into a critical crop domestication process but also adds to the body of knowledge on the molecular mechanism of seed dispersal.